Estimation of the retention behaviour of s-triazine derivatives applying multiple regression analysis of selected molecular descriptors - Jevrić Lidija R.; Podunavac-Kuzmanović Sanja O.; Kovačević Strahinja Z.; Kalajdžija Nataša D.; Jovanović Bratislav Ž. (Acta Periodica Technologica, 2013)
The estimation of retention factors by correlation equations with physico-chemical properties can be of great helpl in chromatographic studies. The retention factors were experimentally measured by RP-HPTLC on impregnated silica gel with paraffin oil using two-component solvent systems. The relationships between solute retention and modifier concentration were described by Snyder’s linear equation. A quantitative structure-retention relationship was developed for a series of s-triazine compounds by the multiple linear regression (MLR) analysis. The MLR procedure was used to model the relationships between the molecular descriptors and retention of s-triazine derivatives. The physicochemical molecular descriptors were calculated from the optimized structures. The physico-chemical properties were the lipophilicity (log P), connectivity indices (χ), total energy (Et), water solubility (log W), dissociation constant (pKa), molar refractivity (MR), and Gibbs energy (GibbsE) of s-triazines. A high agreement between the experimental and predicted retention parameters was obtained when the dissociation constant and the hydrophilic-lipophilic balance were used as the molecular descriptors. The empirical equations may be successfully used for the prediction of the various chromatographic characteristics of substances, with a similar chemical structure. [Projekat Ministarstva nauke Republike Srbije, br. 31055, br. 172012, br. 172013 i br. 172014]